Employment during school and academic performance of Miagao campus-based students of the University of the Philippines Visayas. - Villanueva, Ron G. (2010.)
The study assessed the impact of employment on the academic performance of Miagao Campus-based students of the University of the Philippines Visayas (UPV). Study participants were 57 students without work who belonged to relatively well-off households and 60 students with work either as student assistants or private online tutors. They work to gain experience and to have additional income for social and leisure activities. Parents remain as the main financiers of study participants' college education. Regression results showed that the factors significantly related to academic performance of students, which is measured using the General Weighted Average (GWA), include study hours and working at most 21 hours per week at 1 percent and class hours, social and leisure hours, and sleeping hours at 5 percent. However, based on the R raised to the 2nd power, only 51 percent of the variation in GWA can be explained by the model used. The study recommends that further investigation must be done to further understand the relationship between work and academic performance of UPV students. Similar study can be conducted to include all colleges of UPV.
Thesis (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Students -- University of the Philippines Visayas -- Miagao Campus